1974
DOI: 10.1002/aic.690200221
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and prediction of high‐pressure phase equilibria with a dilute component in the gas phase: The methane‐n‐hexane system

Abstract: The design of vapor recovery processes requires very accurate vaporliquid equilibria data. In this work the problem is attacked from both an experimental and a correlational viewpoint, and the methane-n-hexane system is chosen for study. A predictive model for vapor-liquid equilibrium aids in the interpretation of the experimental measurements, and data acquired in this study agree closely with the theoretical predictions. Maximum deviation between calculated and experimental equilibrium ratios (yi/xi) is 8.5y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The results are shown in Table IV. For comparison, the results obtained from the data of Shim and Kohn (1) and Gunn et al ( 2) are shown In the same (2). It was found that the experimental data and the calculated results agree well with each other.…”
Section: Consistency Testmentioning
confidence: 59%
See 1 more Smart Citation
“…The results are shown in Table IV. For comparison, the results obtained from the data of Shim and Kohn (1) and Gunn et al ( 2) are shown In the same (2). It was found that the experimental data and the calculated results agree well with each other.…”
Section: Consistency Testmentioning
confidence: 59%
“…To evaluate the validity of the experimental procedure, the consistency test of Gunn et al (2) was applied to the data of the methane-n -hexane system. In this test, a vapor-phase mole fraction was calculated from T-P-x data by using the vlrlal equation of state truncated after the second virial coefficient.…”
Section: Consistency Testmentioning
confidence: 99%
“…Of these, the most recent are the works of Shim and Konh, (8) Poston and McKetta, (9) Gun et al, (10) Lin et al (11) and Chylinski et al (6) To compare the data of this study with other investigations, the reports by Shim and Konh (8) and Chylinski et al (6) were chosen as they are the only ones that include data collected at the same temperature and over a similar range of pressures to those obtained in this work. Furthermore, the comparison with Chylinski et al (6) also offers the opportunity to examine the reproducibility of the data, as both sets of data were obtained in the same v.l.e.…”
Section: Experimental Data On (Methane + + + N N N-hexane)mentioning
confidence: 89%
“…Additionally, the components of this mixture also show significant size asymmetry which introduces challenges in the investigation of such mixtures (as discussed later) in the grand canonical ensemble. Extensive experiments as well as equation-of-state calculations have been performed for this mixture, and a large amount of data is available for comparison with molecular simulation results. Industrially, the study of this mixture is important for processes which entail the separation of propane, butane, and natural gasoline from natural gases and, hence, require very accurate predictions of VLE data.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive experiments as well as equation-of-state calculations have been performed for this mixture, and a large amount of data is available for comparison with molecular simulation results. Industrially, the study of this mixture is important for processes which entail the separation of propane, butane, and natural gasoline from natural gases and, hence, require very accurate predictions of VLE data.…”
Section: Introductionmentioning
confidence: 99%